PENGARUH SELF-EFFICACY DAN LEARNING AGILITY TERHADAP READINESS FOR CHANGE DI PT X KOTA CIMAHI - Yudhitia Malle; Indah Soca Retno Kuntari; Gianti Gianti Gunawan (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2026)
This study aims to understand how self-efficacy and learning agility affect readiness for change among employees of PT X in Cimahi City. Readiness for change is the readiness to face changes that occur. This study uses a quantitative method with a cross-sectional design. The sampling method used is disproportionate stratified random sampling, with a total of 106 employees from PT X as respondents. The collected data were processed using multiple regression analysis to determine the effect of self-efficacy and learning agility on readiness for change. The results of the F test showed a significance value of 0.014 (p < 0.05), where self-efficacy and learning agility had a significant effect on readiness for change. The coefficient of determination of 0.615 showed that self-efficacy and learning agility explained 61.5% of the variation in readiness for change, while the remaining 38.5% was influenced by other factors.